Genital Ulcer Disease: A Review of Pathogenesis and Clinical Features. Issue 6 (November 2019) - Maliyar, Khalad; Mufti, Asfandyar; Syed, Maleeha; Selk, Amanda; Dutil, Maha; Bunce, Paul E.; Alavi, Afsaneh
Genital ulcer disease can be caused by a wide variety of sources. Most commonly, genital ulcer disease is grouped into infectious and noninfectious causes. HSV, syphilis, lymphogranuloma venereum, and chancroid represent some common infectious ulcers. Noninfectious causes on the other hand can be inflammatory, noninflammatory, or malignant (eg, squamous cell carcinoma). Depending on the etiology, genital ulcers may present with unique features that can help clinicians identify the etiology and start treatment in a timely manner. The clinical presentation and management of infectious and noninfectious genital ulcers will be discussed in this review.